Surgical Outcomes of Trabeculectomy in Uveitic Glaucoma: A Long-Term, Single-Center, Retrospective Case-Control Study. (21st May 2021) - Kanaya, Rina; Kijima, Riki; Shinmei, Yasuhiro; Shinkai, Akihiro; Ohguchi, Takeshi; Namba, Kenichi; Chin, Shinki; Ishida, Susumu
Abstract : Purpose . To evaluate the long-term outcomes of trabeculectomy with mitomycin C (MMC-TLE) in patients with uveitic glaucoma (UG). Patients and Methods. This was a retrospective, nonrandomized case series study. MMC-TLE was performed on 50 eyes with UG between February 2001 and January 2015 at Hokkaido University Hospital. Age- and sex-matched patients with primary open angle glaucoma (POAG) who underwent MMC-TLE were matched by age and sex and enrolled as controls. Surgical success was defined as an intraocular pressure (IOP) less than 18 or 15 mmHg. The Kaplan–Meier survival curves for surgical failure were analyzed. Results . The mean preoperative IOP in UG and POAG was 27.6 ± 10.6 and 18.0 ± 4.5 mmHg, respectively. After the surgery, the mean IOP in UG and POAG was reduced to 11.7 ± 4.2 and 12.2 ± 3.8 mmHg at 12 months, 11.9 ± 7.0 and 12.1 ± 3.1 mmHg at 36 months, and 13.0 ± 5.2 and 10.6 ± 1.2 mmHg at 120 months, respectively. The success rates (IOP <18 mmHg, IOP reduction >20%) in UG and POAG were 91.7% and 88.0% at 12 months, 82.2% and 75.6% at 36 months, and 66.5% and 61.8% at 120 months, respectively. The success rates (IOP <15 mmHg) in UG and POAG were 64.0% and 58.0% at 12 months, 55.1% and 45.5% at 36 months, and 47.9% and 37.8% at 120 months, respectively. There was no significant difference in the success rate between UG and POAG at 120 months after surgery by either definition of surgical success. Conclusions . MMC-TLE effectively reduced IOP in both UG and POAG. There was no significant difference in the success rate between UG and POAG. Following sufficient inflammation suppression, surgical outcomes of UG may be comparable with those of POAG.